The value of financial advice: An analysis of the investment performance of advised and non-advised individual investors. (28th October 2016) - Allie, Jahangir; West, Darron; Willows, Gizelle
ABSTRACT: This study investigates the value added by financial advisors on the investment performance of advised versus non-advised individuals. A sample of 4 142 individual investors from a large South African investment house were analysed over a period of 10 years from 1 January 2005 to 31 December 2014. The data was analysed to draw conclusions on the return and trading behaviour of investors. The results indicate no statistical difference between the returns generated between advised and non-advised investors. However, advised investors make statistically significantly more trades than non-advised investors. The results indicate that there is no significant additional benefit of utilising a financial advisor, after the initial fund selection decision has been made.